Three-dimensional imaging and computational quantitation as a novel approach to assess nerve fibers, enteric glial cells, mast cells, and the proximity of mast cells to the nerve fibers in human sigmoid mucosal biopsies from healthy subjects - Yuan, Pu-Qing; Li, Tao; Mahurkar-Joshi, Swapna; Sohn, Jessica; Chang, Lin; Taché, Yvette (Journal of neuroscience methods, 2025)
The visualization and quantitation of nerve fibers (NFs), enteric glial cells (EGCs), mast cells (MCs), and their spatial configurations in the human colonic mucosa represent considerable challenges due to the meshed network of these components and the arborizing of NFs in a three-dimensional (3D) structure. We developed a novel approach combining tissue clearing, 3D imaging and computerized quantitation of NFs, EGCs and MCs in sigmoid mucosal biopsies of healthy subjects using a modified CLARITY tissue clearing protocol and adapting Imaris Surfaces Rendering Technology. The cleared colonic biopsies are compatible with immunostaining using 10 marker antibodies and capable of generating 3D images rendering clear spatial views and computational quantitation of NFs, MCs, EGCs, in particular the proximity of MCs to NFs with Imaris 9.7–9.9. Our modified tissue clearing protocol shortened the membrane lipid removal time to 1 day from the original 1–2 weeks and total tissue clearing time to 3–4 days from the original 2–4 weeks. The 3D images displayed a clear spatial landscape of NFs, MCs and EGCs in the biopsies which cannot be portrayed with 2D images acquired from sections. Computerized quantitation is faster than measuring manually, allowing us to quantify a larger number of samples with less bias. The novel approach enables faster tissue clearing/immunolabeling, high-quality 3D imaging and precise computational quantitation of NFs, cells and proximity of MCs to NFs in human sigmoid biopsies which may allow new insight to detect alterations in colonic-related diseases. •Novel method enables rapid tissue clearing, immunolabeling & high-quality 3D imaging of human sigmoid mucosal biopsies.•Automated 3D analysis can quantify nerve fibers, mast cells & their spatial relationships with precision & efficiency.•Intrinsic fibers are denser than extrinsic fibers in healthy sigmoid mucosa, revealed by these techniques.•This novel method can also apply to biopsies from other GI regions to detect disease-related structural changes.